Does the Child Penalty Strike Twice - Mette Gørtz; Sarah Sander; Almudena Sevilla (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
This paper studies the relative labor market outcomes of grandmothers in comparison to grandfathers before and after the arrival of the first grandchild using Danish administrative data and an event study approach. We find that women's labor market outcomes decline at a steeper rate than men's after the arrival of the first grandchild. We find gender gaps in earnings of three and nine percent five and ten years after the arrival of the first grandchild, which is almost exclusively driven by women's reductions in full-time employment. We document that these "grandchild penalties" are larger in periods with more generous retirement options.
Keywords: J13; J14; J16; J22; 330; grandchildren; female labor supply; gender; inequality; retirement